Rapid probing of sialylated glycoproteins in vitro and in vivo via metabolic oligosaccharide engineering of a minimal cyclopropene reporter. Issue 13 (4th March 2015) - Xiong, De-Cai; Zhu, Jingjing; Han, Ming-Jie; Luo, Hui-Xin; Wang, Cong; Yu, Yang; Ye, Yuqian; Tai, Guihua; Ye, Xin-Shan
Abstract : A minimal and efficient cyclopropene chemical handle was identified both in vitro and in vivo . Abstract : ManNAc analogues are important chemical tools for probing sialylation dynamically via metabolic oligosaccharide engineering (MOE). The size of N -acyl and the nature of the chemical handle are two determinants of metabolic incorporation efficiency. We demonstrated a minimal, stable, bioorthogonal, and reactive N-Cp ( N -(cycloprop-2-ene-1-ylcarbonyl)) group and the imaging of sialylated glycans using Ac4 ManNCp in vitro and in vivo . The results revealed that the Cp group can efficiently be incorporated into the cellular sialic acid and detected rapidly by the reaction with FITC-Tz in different cells. The metabolic incorporation efficiency of non-cytotoxic Ac4 ManNCp is not only superior to Ac4 ManNMCp, but also superior to the widely-used Ac4 ManNAz in some cell lines. Moreover, when Ac4 ManNCp was administered to mice, a rapid and intense labelling of splenocytes as well as glycoproteins of sera and organs was observed. This is the first reported metabolic labelling of cyclopropene-modified sugars in vivo . Therefore, Ac4 ManNCp is a powerful probe for efficient and rapid MOE and it may find wide applications in the labelling of glycans.